Temperature and holding time of instrument sterilization as an infection control of odontectomy - Meliawaty, Florence; Mangundjaja, Sunardhi; Hardjawinata, Karlina (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2011)
Odontectomy should be performed aseptically. The goal of sterilization is the complete killing of all forms of microbial life including bacterial spores on the items being processed. Biologic monitoring provides the main guarantee of sterilization. The aim of this study was to find the interrelation of the temperature and the holding time of instrument sterilization as an infection control for the successful of lower molars odontectomy. This experimental laboratory study was conducted at the Oral Maxillofacial Surgery Department in the Hasan Sadikin General Hospital Bandung and at the Microbiology Laboratory Faculty of Dentistry, Universitas Padjadjaran, Jatinangor. The Protocol was performed in three methods of sterilization: dry heat with oven and ozone, dry heat with oven and infrared (125)C for 15 minutes), both were monitored by Bacillus atrophaeus as the biologic indicators, and autoclavization (121